2012
DOI: 10.5121/ijcses.2012.3102
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study analysis of materialized view for selection cost

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…So, the number "44" identifies the participating attributes in this transaction. In the first iteration, since the number of transactions was 18, the minimum support value was chosen to be 6 as already explained and after this iteration, only one frequent set was identified and that was [6,8,12,14,16,18,19] which had the minimum support value of 6, i.e., this set has occurred 6 times in the whole set of transactions as depicted in table 1. In accordance with the reason explained above, this set is identified by the binary number 01101010100010100000 (with the MSB corresponds to the 20 th attribute and the LSB corresponds to the 1 st attribute) which has the equivalent decimal number 436384.…”
Section: Results and Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…So, the number "44" identifies the participating attributes in this transaction. In the first iteration, since the number of transactions was 18, the minimum support value was chosen to be 6 as already explained and after this iteration, only one frequent set was identified and that was [6,8,12,14,16,18,19] which had the minimum support value of 6, i.e., this set has occurred 6 times in the whole set of transactions as depicted in table 1. In accordance with the reason explained above, this set is identified by the binary number 01101010100010100000 (with the MSB corresponds to the 20 th attribute and the LSB corresponds to the 1 st attribute) which has the equivalent decimal number 436384.…”
Section: Results and Analysismentioning
confidence: 99%
“…Similarly, in the second step of the iteration, as shown in table 2, a new set of 18 transactions was considered along with the already considered set and hence in this iteration, the total number of participating transactions was 36 and the minimum support values has been increased to 12 (1/3 rd of 36). 4,5,6,7,8,9,10,11,12,13,14,15,16,17,19 16 1,4,6,8,11,12,14,15,20 17 1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20 18 8 After applying the algorithm, only the set [10,14,16,18] was identified to be materialized, i.e., crossed the threshold value of the minimum support. It was also found that the above-mentioned set has got the minimum support value of 13.…”
Section: Results and Analysismentioning
confidence: 99%
See 3 more Smart Citations